2023
DOI: 10.1101/2023.02.15.528739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copper drives prion protein phase separation and modulates aggregation

Abstract: Prion diseases are characterized by prion protein (PrP) transmissible aggregation and toxicity in the brain. The physiological function of PrP seems related to sequestering and internalization of redox-active Cu2+. It is unclear whether Cu2+contributes to PrP aggregation, recently shown to be mediated by PrP condensation. We investigated the role of Cu2+and oxidation in PrP condensation and aggregation using multiple biophysical and biochemical methods. We find that Cu2+promotes PrP condensation at the cell su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
2
2
0
Order By: Relevance
“…Given that Grh1 liquid condensation is significantly enhanced in response to acidification and most unconventional secretion events are not constitutive but stress-induced [2], we proposed that the CUPS could represent a phase-separated structure formed by a Grh1-rich phase capable of recruiting UPS cargo. Accordingly, the detected amyloid signature previously observed in cell [26] might be attributable to droplet ageing, a property observed previously in other well-known amyloidogenic proteins [4648]. We showed here that Grh1 LLPS is fully reversible, enhanced under starvation conditions, and notably diminished under normal conditions, which are observations aligning with the CUPS dynamics observed in vivo [24].…”
Section: Resultssupporting
confidence: 89%
“…Given that Grh1 liquid condensation is significantly enhanced in response to acidification and most unconventional secretion events are not constitutive but stress-induced [2], we proposed that the CUPS could represent a phase-separated structure formed by a Grh1-rich phase capable of recruiting UPS cargo. Accordingly, the detected amyloid signature previously observed in cell [26] might be attributable to droplet ageing, a property observed previously in other well-known amyloidogenic proteins [4648]. We showed here that Grh1 LLPS is fully reversible, enhanced under starvation conditions, and notably diminished under normal conditions, which are observations aligning with the CUPS dynamics observed in vivo [24].…”
Section: Resultssupporting
confidence: 89%
“…Given that Grh1 condensation is significantly enhanced in response to acidification and most unconventional secretion events are not constitutive but stress-induced (Rabouille, 2017), we proposed that the CUPS could represent a phase-separated structure formed by a Grh1-rich phase capable of recruiting UPS cargo. Accordingly, the detected amyloid signature previously observed in cell (Fontana et al, 2021) might be attributable to a liquidto-solid transition, a property observed previously in other well-known amyloidogenic proteins (Amaral et al, 2023;Carey & Guo, 2022;Ray et al, 2020). We showed here that Grh1 coacervates were fully reversible, enhanced under starvation conditions, and notably diminished under normal conditions, which are observations aligning with the CUPS dynamics observed in vivo (Bruns et al, 2011).…”
Section: Cups As a Grh1 Enriched Phaseseparated Condensate?supporting
confidence: 90%
“…Previous studies have utilized homoFRET to identify and characterize membrane-induced clustering and oligomerization in vitro as well as in membrane-anchored proteins in situ 65 . HomoFRET imaging can be employed to investigate membrane-associated phase separation of membrane-bound proteins 66,67 . Recent studies have shown the tuning of FUS condensates and their material properties by the protein quality control (PQC) machinery, including small heat shock proteins and chaperones 68,69 .…”
Section: Discussionmentioning
confidence: 99%